Assessment of Health Risk of Exposure to Alpha-Emitters in Cheese Samples Collected from Iraqi Markets - R. R. Muneam; A. A. Abojassim (Atom Indonesia, 2023)
In this research, alpha-emitter concentrations of 222Rn, 226Ra, and 238U in Iranian, Turkish, Egyptian, Saudi Arabian, and Iraqi canned cheeses that are available in Iraqi markets were measured using the CR-39 detector. Also, the health risk parameters associated with the ingestion of alpha-emitter radionuclides, such as the annual average internal effective dose (AAIED) and the risk of an excess cancer fatality per million persons (RECFPMP), were calculated. The results show that the average values of 222Rn, 226Ra, and 228U concentrations for all samples in the present study were 3.7±0.38 Bq/m3, 25.24±2.63 mBq/kg, and 0.025±0.002 ppm, respectively. The average values of AAIED and RECFPMP were 0.175±0.018 µSv/y and 0.674±0.070, respectively. The results show that the highest value of alpha-emitters as well as health risk parameters were found in cheese samples produced in Saudi Arabia, while the lowest results were found in Egyptian samples. They were, nevertheless, less than the permissible value and the risk value. According to the current study, the consumption of those cheese products poses no health risks.